Implementasi Konservasi Moral Melalui Pendidikan Akuntansi Berkarakter Untuk Mengoptimalkan Peran Etika Bisnis Dan Profesi Dalam Upaya Mewujudkan Greening Business Management - Maylia Pramono Sari; Surya Raharja (Conference In Business, Accounting, And Management (CBAM), 2012)
There are some very facts related to the environmental crisis that occurred in Indonesia. Environmental crisis facing humanity is a direct result of environmental management â€œnon-ethicalâ€. Thus it can be said that the ecological crisis facing humanity is rooted in a crisis of ethics or moral crisis largely caused by the neglect of character education. Therefore, in order to achieve Greening Business Management is a strategy of integrated environmental management will require optimization of business ethics and professional roles in business processes.The growth of ethical awareness is influenced by a person during oneâ€™s college education. Therefore, it is necessary to raise awareness of the role of education through the implementation of conservation ethical moral in all subjects in the curriculum. If it is also applied to S1 accounting students, the students will become professionals in the field of accounting that have ethical considerations ability is fine as it used to take ethical considerations in both the professional as well as discussion of ethical dilemmas through simulation completion of cases of ethical considerations. The author conducted a conceptual study in the writing of this article and the author seeks to analyze alternative solutions to the problems existing environmental crisis. The authors sought to implement conservation through learning accounting moral character throughout the course to the curriculum S1 Accounting, by taking an example of the study of the curriculum of the Faculty of Economics in Accounting S1 Semarang State University in 2012 with a total of 66 subjects. Real steps by the author is to redesign the competency standards in all accounting courses by optimizing the four aspects of intelligence that is Physic Quotient (PQ), Intellectual Quotient (IQ), Emotional Quotient (EQ) and Spiritual Quotient (SQ) to generate student character positive. Expected with positive character formation of the students, it is expected the perpetrators accounting accounting will also have a good character in the business-related issues so expect moral and character primarily related to the environmental crisis will be resolved and the business can be runÂ with a healthy, consistent and ethical.In this case, the authors classify as accounting actors in the formation of character is the focus of financial accountants, management accountants, public accountants, public sector accountants, managers and stakeholders of the company. The results showed that of the 66 subjects, there were 35 subjects that are the focus of character education for character building accountants, managers and stakeholders; 13 subjects were the focus of financial accountants, public accountants and public sector accountants, 11 subjects were focused management accountant, 7 subjects that focus accountants public and public sector accountants.Keywords: Greening Business Management, Business & Profession Ethics, Learning Accounting Character, Moral Conservation